Understanding sustainable curriculum: The impact of designer teaching climate on student self-efficacy and academic self-control - Yazgan, Akan Deniz; Kartal, Osman Yılmaz; Temelli, Dinçer; Kartal, Meral Yavuz (International Journal of Innovative Research and Scientific Studies, 2025)
The concept of “designer teaching” has emerged as a promising approach to fostering student success by creating engaging and relevant learning experiences that are tailored to the diverse needs and capabilities of learners, aiming to provide and impart knowledge effectively to them. Hence, this study investigates the impact of designer teaching climates on student outcomes, specifically self-efficacy and academic self-control, within the context of sustainable learning environments that are influenced by design. Using the quantitative correlational research design that involves careful collection, analysis, and presentation of data, a sample of 445 secondary school students and 65 teachers was effectively selected from schools characterized by moderate-to-high levels of academic achievement, which offer a good basis for the establishment of a designer teaching climate. Thus, data were collected using the Academic Self-Control Scale, the Self-Efficacy Questionnaire for Adolescents, and the Designer Teacher Scale to accurately measure the outcomes and assess the way students and teachers perceive the learning ecosystem. Consequently, a one-way multivariate analysis of covariance (MANCOVA) was conducted to examine the relationship between designer teaching climate and student outcomes, controlling for grade level and gender in order to capture all the relevant factors and influence the teacher-student relationship in a proper manner. The findings were indeed significant and revealed that a designer teaching climate had a significant positive effect on students’ self-efficacy but not on their academic self-control, since the former appreciated the teacher’s efforts in enhancing their performance, unlike the latter. However, gender differences were observed in both self-efficacy and academic self-control, which suggests that the perception of designer teaching climate differs between boys and girls, with girls reporting higher levels of academic self-control than boys while they equally perform well in self-efficacy. Furthermore, grade level had a significant effect on self-efficacy, with older students reporting higher levels of self-efficacy than younger students, thus indicating incremental advancement and psychological development on the part of the learner. The study highlights the importance of fostering a designer teaching climate that promotes student self-efficacy and academic self-control, thus enabling them to have a mental orientation, drawing from past experiences, and feeling capable of achieving academically and controlling their academic focus. By creating engaging and relevant learning experiences, designer teachers can empower students to overcome their challenges, academically excel, and unleash their full potential that they did not even think they could achieve. The observed gender and grade level differences underscore the need for differentiated instruction and support that addresses the unique needs of all learners, thus ensuring that every student receives the necessary support to be productive.